Is alectinib the new first line therapy in ALK-rearranged advanced non-small cell lung cancer? - van der Wekken, Anthonie J.; Kok, Klaas; Groen, Harry J. M. (Journal of Thoracic Disease; Vol 10, Supplement 18 (July 18, 2018): Journal of Thoracic Disease, 2018)
Since the registration of crizotinib for ALK-positive NSCLC in 2010, the landscape of testing and drug development has changed enormously (1). Fluorescence in situ hybridization (FISH) has been used as golden standard for a long time. However, recently ALK-IHC (immunohistochemistry) with D5F3 antibody showed to be a better predictor of tumor response to crizotinib than FISH (2). Therefore, D5F3 has been used in most recently conducted clinical trials and is one of the most favorable tests to screen for ALK in non-squamous NSCLC at this moment.